Designs for Experimentation and Inquiry Approaching Learning and Knowing in Digital Transformation - Mäkitalo, Åsa; Nicewonger, Todd E.; Elam, Mark (Taylor & Francis, 2019)
Designs for Experimentation and Inquiry examines how digital media is reconfiguring the established worlds of research, education and professional practice. It reflects on the theoretical, methodological and ethical issues shaping contemporary engagements with digital learning and offers insights for both analysing and intervening in digital learning practices. This insightful volume fills a gap in the current literature by bringing together experiences from Sociocultural Studies of Learning, Science and Technology Studies, and Design Studies. Each chapter is an innovative case study, examining a different aspect of digital media's role in research, education and professional practice by exploring topics such as: Learning practices and digitalized dialogue Digital design experiments Digitally mediated collaborations Ethical digital inquiry and design Expertly researched and written, this book is a unique resource for scholars, researchers and professionals working in the fields of digital design, applied technology and the learning sciences.